Estudio de mejora en mi tienda online Belcorp - Bellido Ortega, Andrea Maria (2021)
This work is focused on implementing a digital tool for Belcorp consultants. It is important to first define a value proposition for the consultants, for which it was defined that this tool complements its traditional business, generating a profit of between 20% and 40% depending on the sale amount. It was also defined that it would not add to the incentives of the consultants, which allows a contribution margin of up to 38% and makes it a profitable tool. To carry it out, it was necessary to implement a digital ecommerce tool, which reflects the same products the catalog has and in which the consultant can put her personal information to personalize it. Customers had to pay online, so a gateway with different payment methods was implemented and, in addition, simple navigation was defined through a search tool and product categories. This platform is achieving in less than 1 year more than 2 million sessions and more than 17 thousand orders. Additionally, a supply chain process was implemented, with a Courier and assembly line different from those of direct sales, to ensure the immediacy in the delivery of products to customers. On the customer service side, a process was also designed in which both consultants and clients of Mi Tienda Online would be attended, with a specific CRM typification, which has successfully handling more than 2 thousand calls by October. Finally, the staggered communication strategy that was implemented for the different audiences (sales force and consultants) will be reviewed, emphasizing the benefits of the tool and some promotions. The strategy was based mainly on workshops, mailing and sending SMS, which allowed reaching, with conviction, 100% of the sales force and more than 50% of consultants firms in the country.